Pengaruh Gaya Kepemimpinan, Kompetensi dan Lingkungan Kerja terhadap Kinerja Guru - Sinta Apriliani; Asih Handayani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research was conducted on teachers of SMAN 1 Ngrambe Kabupaten Ngawi the type of data used was quantitative data. The data source used is primary data. The population in this study was 45 teachers from SMAN 1 Ngrambe Kabupaten Ngawi. The sample in this study amounted to 45 teachers using saturated sampling. Data collection techniques using questionnaires. Data analysis techniques use multiple linear regression analysis, descriptive analysis, t test, F test and determination coefficient test. The results showed that leadership style had an insignificant effect on teacher performance, competence had a significant effect on teacher performance, and the work environment had an insignificant effect on teacher performance. The result of the coefficient of determination is 0.725 This means that the magnitude of the influence of independent variables of leadership style (X1), competence (X2) and work environment (X3) on variables tied to teacher performance (Y) at SMAN 1 Ngrambe Kabupaten Ngawi is 72.5%, while the rest (100% - 72.5%) = 27.5% is explained by other variables outside the model such as work discipline, work motivation, work stress and others.